Consumers' propensity to resist: A contribution to the study of the Disposition to oppose market influence attempts. (June 2014) - Banikema, Annie Stéphanie; Roux, Dominique
The purpose of this article is to propose a dispositional approach to consumers' propensity to resist (CPR) that could predict critical behaviors in the marketplace. A literature review and a qualitative study are used to delineate the construct and its two dimensions – self-affirmation and self-protection. A measurement scale is then developed using four samples, two of which are representative. This data collection from 1721 individuals enables us to construct a final model that validates the relationships between the two dimensions of the CPR scale, its psychological antecedents and its effects on various consumption behaviors and critical orientations toward the market.